Pengaruh Rekrutmen dan Pelatihan Terhadap Kinerja Karyawan di Penguruan Tinggi XYZ Jakarta Timur - Enjang Hidayat; Ignatius Ario Sumbogo (UNIVERSITAS KALBIS, 2022)
This study aims to determine the effect of recruitment and training on employee performance at XYZ College in East Jakarta. Field research method with quantitative approach. Employee population 150 people with a sample of 50 people. The sampling technique is non-probability sampling with the type of random sampling. Data processing using multiple linear regression using SPSS Version 25 software. The results of this study conclude that there is no direct effect of recruitment on performance, there is a significant effect of training on performance and simultaneously recruitment and training have a significant effect on performance.